2022
DOI: 10.3390/molecules27082443
|View full text |Cite
|
Sign up to set email alerts
|

Excited-State Intramolecular Proton Transfer Dyes with Dual-State Emission Properties: Concept, Examples and Applications

Abstract: Dual-state emissive (DSE) fluorophores are organic dyes displaying fluorescence emission both in dilute and concentrated solution and in the solid-state, as amorphous, single crystal, polycrystalline samples or thin films. This comes in contrast to the vast majority of organic fluorescent dyes which typically show intense fluorescence in solution but are quenched in concentrated media and in the solid-state owing to π-stacking interactions; a well-known phenomenon called aggregation-caused quenching (ACQ). On … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(39 citation statements)
references
References 115 publications
0
39
0
Order By: Relevance
“…8–10 The excitation of such a molecule in its normal form ( N ) with light results in the transfer of the electron density from the electron-donating group to the electron-accepting one, which in turn alters the acidity and basicity of the proton-donating and proton-accepting groups and promotes the proton to transfer (excited state intramolecular proton transfer, ESIPT) affording the tautomeric form ( T ) of the molecule (Scheme 1). 11–32 If the ESIPT process is barrierless, the only form to emit is the tautomeric form. This emission is associated with dramatic reorganization of the molecular structure, resulting in large Stokes shifts.…”
Section: Introductionmentioning
confidence: 99%
“…8–10 The excitation of such a molecule in its normal form ( N ) with light results in the transfer of the electron density from the electron-donating group to the electron-accepting one, which in turn alters the acidity and basicity of the proton-donating and proton-accepting groups and promotes the proton to transfer (excited state intramolecular proton transfer, ESIPT) affording the tautomeric form ( T ) of the molecule (Scheme 1). 11–32 If the ESIPT process is barrierless, the only form to emit is the tautomeric form. This emission is associated with dramatic reorganization of the molecular structure, resulting in large Stokes shifts.…”
Section: Introductionmentioning
confidence: 99%
“…Organic fluorophores whose emission is as effective in solution at low concentration as for aggregates, powders or crystals, now frequently termed dual-state emission (DSE) derivatives, have attracted much attention in the last decade. [1][2][3] The design of DSE molecules represents a fascinating challenge since it is necessary to circumvent the two antagonistic phenomena which are the quenching of emission for the solid state frequently called aggregationcaused quenching (ACQ) and conversely the emission essentially for the solid state, solid state luminescence enhancement (SLE), often defined by the term aggregationinduced emission (AIE) coined by B. Z. Tang et al [4][5][6] Often ACQ is observed for rigid and planar derivatives that present high luminescence in dilute solution while in the solid state the quenching of emission occurs due to active non-radiative pathways via phenomena such as cofacial π-π interactions and the presence of trap states which are always discussed.…”
Section: Introductionmentioning
confidence: 99%
“…In solution, proton transfer processes such as ESIPT might trigger a large panel of excited‐state dynamics, including deactivation through accessible conical intersection (CI) and hence strong fluorescence quenching. Several studies have consequently reported synthetic strategies to increase solution‐state fluorescence and engineer dual‐state emission ESIPT fluorophores displaying intense emission in both solution and solid [19] . For example, enhancing molecular rigidity in derivatives like imidazo[1,2‐ f ]phenanthridine [20] or 3,5‐ethynyl‐hydroxyphenyl‐benzazole [21–23] has appeared as a straightforward synthetic trick to reduce non‐radiative deactivations through the well‐known “twisting CI”.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have consequently reported synthetic strategies to increase solutionstate fluorescence and engineer dual-state emission ESIPT fluorophores displaying intense emission in both solution and solid. [19] For example, enhancing molecular rigidity in derivatives like imidazo[1,2-f]phenanthridine [20] or 3,5-ethynyl-hydroxyphenyl-benzazole [21][22][23] has appeared as a straightforward synthetic trick to reduce non-radiative deactivations through the well-known "twisting CI". A recent alternative includes the incorporation of pyridinium units onto the HBO scaffold to stabilize the K* species by resonance effects, leading to drastic enhancement of fluorescence intensity in solution.…”
Section: Introductionmentioning
confidence: 99%